(untitled) (Research, Society and Development, 2020)
The objective of this work was to characterize the thermal performance of a steam generator with the intention of reducing the waste of fuel and the costs involved. The economic and social potential of a country is closely related to its energy reserve and the way it is exploited. Development causes significant environmental impacts, the majority being due to the generation and use of energy, of which the demand has become increasingly large. The methodology used was the analysis of an industrial boiler of the ATA 14 H 3N pyrotubular type, of the ATA brand, with a capacity of 33.3 kg / s of steam and a pressure of up to 1034 kPa, fueled by solid fuel (eucalyptus firewood trunks). Data needed for the analysis were obtained through field measurements and chemical analysis reports prepared by specialized companies. The result of the thermal efficiency of the boiler was obtained, by the indirect method, around 74%. It has been concluded that in order to improve the efficiency of the boiler it will be necessary to optimize the excess air, as well as the isolation of more stretches of the steam line and the installation of condensate traps in distant points from the steam generation center.